Kemunculan Perlombaan Antariksa Bernuansa Ekonomi - Deden Habibi Ali Alfathimy (Intermestic: Journal of International Studies, 2017)
Space race is an important part of the Cold War period between the United States and the Soviet Union. Although the race was over, in recent years, there are some indications of the birth of space race with new nuances. New global actors emerge and change the global launch industry arrangement. That is interesting to be studied because the development of space technology is now increasingly affecting the lives of the global community. This paper explains the current space race so that Indonesia gets an idea of ​​new opportunities, both as customers and developers. The method used is qualitative-descriptive. This paper concludes that space race is coming back with more dominant economic nuances through the changing of global political-economy structure in satellite launch industry sector.